Perancangan Dan Pembuatan Sistem Informasi Akuntansi Pada Kedai Kopi Mitra Bersama - Calvina Hartanto (ConCEPt - Conference on Community Engagement Project, 2021)
Micro, Small, and Medium Enterprises (MSMEs) do not require high skills and are easily outperformed by competitors, as is the case with Kedai Kopi Mitra Bersama. Kopi Mitra Bersama doesn’t have an accounting recording system. Financial transaction was recorded manually on cash receipts and disbursements on a daily basis without any data on inventories used, what makes the entity’s profit or loss can’t be known with certainty. After conducting observation and interview method, writer has designed a simple accounting information system that can produce financial reports in accordance to SAK EMKM on the basis of Microsoft Office Access to solve problems with business financial recording and reporting. The designed system has been implemented and can assist the owner in knowing business conditions and financial information. In addition, the recommendation for the next writer is to add cash flow statements feature so that the owner can know directly the cash inflow and outflow that occur in a certain period.